MOOD IMPAIRMENTS IN ADULTS WITH DEVELOPMENTAL COORDINATION DISORDER - SANKAR U, GANAPATHY; R, MONISHA; DOSS, CHRISTOPHER AMALRAJ VALLABA; RM, PALANIVEL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Data on the consequences of adults with developmental coordination disorder (DCD) in their life span is in debate and there is no clear and significant data remains. The current study was done to examine the existence or absence of mood impairments with DCD adults. Methodology: Beck depression and Spielberger Anxiety Inventories were used as an outcome measure to evaluate the symptoms of anxiety and depression in 20 adults diagnosed with DCD with 20 typically developed peer-group population was used as a control. Results: After statistical evaluation, it has been proved that adults with DCD experience enhanced symptoms of depression, anxiety than their age-matched peers. Conclusion: This finding has added evidence that adults with DCD experience psychiatric distress and there is a need for consideration of intervention in DCD.